The influence of work-family conflict and fear of success on affective commitment, mediated by self-efficacy and moderated by intrinsic motivation - Wardhani, Diana Pramudya; Sudiro, Achmad; Irawanto, Dodi Wirawan; Hadiwidjojo, Djumilah (Edelweiss Applied Science and Technology, 2025)
This research aims to analyze the role of self-efficacy in the relationship between work-family conflict, fear of success, and affective commitment, with intrinsic motivation as a moderator. The study employs an explanatory research design to explore potential cause-and-effect relationships among these variables. The independent variables include work-family conflict and fear of success, while the dependent variable is affective commitment. Self-efficacy serves as a mediating variable, and intrinsic motivation functions as a moderating variable in this analysis. This study addresses the research problems by dividing them into three parts: (1) work-family conflict has a negative and significant impact on self-efficacy and affective commitment; (2) fear of success has a negative and significant impact on self-efficacy and affective commitment; (3) self-efficacy mediates the relationship between work-family conflict and affective commitment, as well as between fear of success and affective commitment. The focus of the study is on the population of female police officers in Polwil Madiun, comprising 300 individuals. The sample for this research consists of 172 respondents, selected through purposive sampling based on specific criteria: being married, having children, and possessing more than five years of work experience. Data collection was conducted using a questionnaire utilizing a 5-point Likert scale, and the results were analyzed through structural equation modeling (SEM) software, specifically the Partial Least Squares (PLS) method. The findings indicate that work-family conflict has a negative and significant impact on self-efficacy and affective commitment. Similarly, fear of success negatively influences both self-efficacy and affective commitment. Conversely, self-efficacy has a positive and significant impact on affective commitment. The study confirms that self-efficacy mediates the influence of work-family conflict and fear of success on female police officers’ affective commitment. Additionally, intrinsic motivation moderates the impact of work-family conflict and fear of success on affective commitment. In conclusion, the study reveals that work-family conflict and fear of success negatively and significantly affect self-efficacy and emotional commitment among female police officers. However, high levels of self-efficacy and intrinsic motivation can mitigate these adverse effects, enabling officers to maintain their emotional commitment to their organization.